El aprendizaje organizacional y los proyectos educativos. Un enfoque estratégico. (2004)
The purpose of this research was to generare theoretical and methodological guidelines for the development of an educational project aiming at improving educational quality  and supporting, organizational learning through the application of strategic planning in schools. The study adopted a humanistic,  critical perspective and applied qualitative design with emphasis in action research, Information gathering techniques were document analysis, in depth interviews, participative observation, diagnosis and surveys.